PENANAMAN SIKAP NASIONALISME DAN GEMAR MEMBACA MELALUI MATA PELAJARAN BAHASA INDONESIA - Adrianus; Latif (Universitas Negeri Medan, 2025)
Abstract: This study aims to describe the teacher's efforts in instilling an attitude of nationalism and love of reading in Indonesian language subjects in class IV of SDN Negeri 017 Jaya Kopah. Indonesia class IV SDN Negeri 017 Jaya Kopah. This study combines a descriptive method with a qualitative approach. The following methods of gathering data are employed: documentation, interviews, and observation. Data reduction, data display, and conclusion drafting were the methods used for data analysis. The results showed that teachers try to instill an attitude of nationalism through integrating national values in learning materials, learning media, the use of national songs, and assignments related to nationalism. learning materials, learning media, the use of national songs, and assignments related to Indonesian culture. with Indonesian culture. Meanwhile, to foster a love of reading is done through interest and motivation to read, paying attention to the frequency and duration of reading, exposure to various types of texts in Indonesian language subjects, including narrative texts, descriptions, poetry, and information related to national culture and history. culture and history of the nation. Keywords: Cultivation, Nationalism Attitude, Love to Read Abstrak: Penelitian ini berujuan untuk menjelaskan upaya guru dalam menumbuhkan sikap nasionalisme serta kecintaan membaca pada mata pelajaran bahasa Indonesia di kelas IV SDN Negeri 017 Jaya Kopah. Penelitian ini memakai pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data yang digunakan meliputi observasi, wawancara, dan dokumentasi. Analisis data dilakukan melalui reduksi data, penyajian data, dan penarikan simpulan. Hasil penelitian ditemukan jika guru berupaya menanamkan sikap nasionalisme melalui pengintegrasian nilai-nilai kebangsaan dalam materi pembelajaran, media pembelajaran, penggunaan lagu-lagu nasional, dan penugasan yang berkaitan dengan budaya Indonesia. Sedangkan untuk menumbuhkan gemar membaca dilakukan melalui minat dan motivasi membaca, memperhatikan frekuensi dan durasi membaca, paparan terhadap berbagai jenis teks dalam mata pelajaran Bahasa Indonesia, termasuk teks narasi, deskripsi, puisi, dan informasi yang berkaitan dengan kebudayaan dan sejarah bangsa. Kata Kunci: Penanaman, Sikap Nasionalisme, Gemar membaca